Reflections of medicolegal aspect of visum et repertum in criminal injury cases according to police investigator as law enforcement in mataram - Syamsun, Arfi; Rahayuningrum, Nurekayani; Rohadi; Herlina, Lenny; Harahap, Ida Lestari; Pujiarrohman (Faculty of Medicine Universitas Mataram, 2020)
Background: To seek evidence for the sake of criminal matters, doctors can act as an expert and create Visum et Repertum. There are various procedures for writing the report of Visum et Repertum due to the lack of formal rules and regulation of Visum et Repertum structure in Indonesia. This condition can confuse and mislead people who use Visum et Repertum such as police investigators. Method: This research is a qualitative descriptive study using cross sectional research design. The sampling technique used is saturated sampling. Data were taken using Medicolegal Aspect Visum et Repertum Reflection questionnaire in the Criminal Case From Law Enforcement Perspectives in Mataram City which was validated. This research analyzed with descriptive qualitative inductive data analysis techniques. The research subjects consisted of 22 police investigators and assistant investigators in the Kepolisian Resor Kota Mataram. Result: From 46 questions regarding the formal and material requirements for Visum et Repertum contained in the questionnaire, 14 of the 46 questions showed the same opinion related to the reflections of the medicolegal aspects of the Visum et Repertum between investigators and assistant investigators. While the opinion of the other 32 questions shows the wide variety of opinions of the investigator and the assistant investigator. Conclusion: There is a difference of opinion related to the reflections of the medicolegal aspects of Visum et Repertum from the perspective of the investigator as a law enforcer in the city of Mataram, which includes formal completeness standards and material completeness standards of Visum et Repertum.